1998
DOI: 10.1136/hrt.80.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transposition of the great arteries in the era of atrial inflow correction

Abstract: Objective-To examine long term morbidity and mortality following atrial inflow corrective procedures for transposition of the great arteries (TGA) and to investigate factors that influence morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…9,12 Table 2 displays the distribution of various congenital heart lesion diagnoses that lead to heart transplantation within the PHTSG/Cardiac Transplant Research Database. 66 Singleventricle lesions, [67][68][69][70] D-transposition of the great vessels (especially after the Mustard or Senning procedure), 71,72 and corrected or L-transposition of the great vessels, 73 lesions known to be associated with risk of ongoing deterioration into adulthood, are not surprisingly common diagnoses that lead to heart transplantation.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…9,12 Table 2 displays the distribution of various congenital heart lesion diagnoses that lead to heart transplantation within the PHTSG/Cardiac Transplant Research Database. 66 Singleventricle lesions, [67][68][69][70] D-transposition of the great vessels (especially after the Mustard or Senning procedure), 71,72 and corrected or L-transposition of the great vessels, 73 lesions known to be associated with risk of ongoing deterioration into adulthood, are not surprisingly common diagnoses that lead to heart transplantation.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…We have not described data on operation technique. Several studies have shown that the type of operation, the year of birth, and era of operation influence late outcome in Mustard and Senning patients (9,10). To exclude the influence of these factors, we matched SD cases and controls for these variables and have, in addition, used controls operated and followed-up in the same center and surgeon as the corresponding SD case.…”
Section: Discussionmentioning
confidence: 99%
“…While their survival rate has been good (1-7), arrhythmia, right ventricular (RV) dysfunction, and late death are well-recognized complications (1)(2)(3)(4)(5)(6)(7)(8)(9). One cause of late death is sudden death (SD) with an incidence of 2% to 15% (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It was the most common cause of late death in some studies (1,2,8).…”
mentioning
confidence: 97%
“…[2][3][4][5][6][7][8][9][10][11][12][13] All but one of these 12 collected data from single centres, thus overlooking the variability inherent in clinical practice, in particular the different surgical techniques applied in these cases. Moreover, the follow up period in most of these studies was limited to approximately 20 years after atrial repair.…”
mentioning
confidence: 99%